EKSPLORASI KESULITAN SISWA: ANALISIS PEMAHAMAN KONSEPTUAL TENTANG PERTIDAKSAMAAN LINEAR DUA VARIABEL [EXPLORING STUDENT DIFFICULTIES: ANALYSIS OF CONCEPTUAL UNDERSTANDING OF TWO-VARIABLE LINEAR INEQUALITIES] - Zulfa Nur Jannah; Fuad Luky Atmaja; Aprilia Wafik Asisha; Melvin Natalia Dwianggraeni (JOHME: Journal of Holistic Mathematics Education, 2025)
This study employed a descriptive qualitative approach to analyze high school students’ conceptual understanding of Two-Variable Linear Inequality (PtLDV) problems. Conceptual understanding constitutes a core component of mathematical proficiency. Three students were selected through purposive sampling based on their problem-solving abilities. Data were collected using written tests, interviews, and documentation. The instruments were designed to measure three indicators of conceptual understanding: (1) the ability to restate concepts, (2) the capacity to present concepts through multiple mathematical representations, and (3) the ability to apply concepts or algorithms in problem-solving contexts. Data analysis followed the Miles and Huberman model. The findings indicate that two students demonstrated a high level of conceptual understanding, meeting all indicators, whereas one student exhibited a low level of understanding, particularly in relation to problem context and mathematical modeling. These results underscore the need to design adaptive learning strategies to support students with conceptual gaps and suggest that future studies using mixed-methods designs may yield deeper insights into this issue. BAHASA INDONESIA ABSTRACT: Penelitian ini menggunakan pendekatan kualitatif deskriptif untuk menganalisis pemahaman konseptual siswa sekolah menengah atas tentang masalah Pertidaksamaan Linear Dua Variabel (PtLDV). Pemahaman konseptual merupakan landasan kemahiran matematika. Tiga siswa dipilih sebagai subjek dengan menggunakan purposive sampling berdasarkan kemampuan pemecahan masalah. Data dikumpulkan melalui tes tertulis, wawancara, dan dokumentasi. Instrumen disusun untuk menilai tiga indikator pemahaman konseptual: (1) kemampuan menyatakan ulang konsep, (2) keterampilan menyajikan konsep dalam berbagai representasi matematis, dan (3) kompetensi menerapkan konsep atau algoritma untuk pemecahan masalah. Model Miles dan Huberman digunakan sebagai panduan dalam proses analisis data. Hasil penelitian menunjukkan bahwa dua siswa mencapai tingkat pemahaman yang tinggi, memenuhi semua indikator konseptual. Sebaliknya, satu siswa menunjukkan tingkat pemahaman yang rendah, menunjukkan kesulitan khusus dengan konteks masalah dan pemodelan matematika. Temuan ini menyoroti pentingnya merancang strategi pembelajaran adaptif untuk membantu siswa dengan kesenjangan pemahaman dan menyarankan agar pendekatan metode campuran dalam penelitian di masa depan dapat memberikan eksplorasi yang lebih mendalam tentang masalah ini.